Geopolitical Tensions In The Modern World: A Comprehensive Global Risk Analysis And The Path Forward For International Diplomacy - Saipiatuddin; Kristian, Indra; Sari, Ananda Rivaldo; Rifaldi, Muhammad Rizal; Hendarto, Totok (International Journal of Science and Society, 2024)
Geopolitical Tensions In The Modern World Have Become A Major Concern For Countries Around The World, Fueled By Shifts In Economic And Military Power, As Well As Intensifying Competition For Resources. These Dynamics Are Complicated By The Impact Of Technology And Innovation, As Well As Regional Instability That Affects Global Security And Prosperity. Emerging Conflicts And Crises Demand New Approaches In International Diplomacy To Promote Peace And Stability. This Research Aims To Comprehensively Analyze The Global Risks Posed By Geopolitical Tensions And Explore The Way Forward For International Diplomacy. This Research Uses A Qualitative Approach, With Data Obtained From Previous Research Results And Related Studies To Gain In-Depth Insight Into This Issue. The Results Of This Research Show That Geopolitical Tensions Require A Collaborative And Innovative Global Response, With International Cooperation And Strengthening International Institutions As The Main Key. The Future Of International Diplomacy Depends On Adapting To The Digital Era, Effectively Utilizing Soft Power, And Creating New Models Of Cooperation That Can Address The Challenges Of The 21st Century. The Importance Of Commitment To International Dialogue And Cooperation Was Emphasized, As The Main Means Of Creating Sustainable Global Peace And Security. Success In Overcoming Geopolitical Tensions Will Determine The Stability And Progress Of Humanity In The Future.